Hospital at home: home-based end of life care. - Shepperd, S; Wee, B; Straus, SE (2011)
BACKGROUND: The policy in a number of countries is to provide people with a terminal illness the choice of dying at home. This policy is supported by surveys indicating that the general public and patients with a terminal illness would prefer to receive end of life care at home. OBJECTIVES: To determine if providing home-based end of life care reduces the likelihood of dying in hospital and what effect this has on patients' symptoms, quality of life, health service costs and care givers compared with inpatient hospital or hospice care. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library) to October 2009, Ovid MEDLINE(R) 1950 to March 2011, EMBASE 1980 to October 2009, CINAHL 1982 to October 2009 and EconLit to October 2009. We checked the reference lists of articles identified for potentially relevant articles. SELECTION CRITERIA: Randomised controlled trials, interrupted time series or controlled before and after studies evaluating the effectiveness of home-based end of life care with inpatient hospital or hospice care for people aged 18 years and older. DATA COLLECTION AND ANALYSIS: Two authors independently extracted data and assessed study quality. We combined the published data for dichotomous outcomes using fixed-effect Mantel-Haenszel meta-analysis. When combining outcome data was not possible we presented the data in narrative summary tables. MAIN RESULTS: We included four trials in this review. Those receiving home-based end of life care were statistically significantly more likely to die at home compared with those receiving usual care (RR 1.33, 95% CI 1.14 to 1.55, P = 0.0002; Chi (2) = 1.72, df = 2, P = 0.42, I(2) = 0% (three trials; N=652)). We detected no statistically significant differences for functional status (measured by the Barthel Index), psychological well-being or cognitive status, between patients receiving home-based end of life care compared with those receiving standard care (which included inpatient care). Admission to hospital while receiving home-based end of life care varied between trials and this was reflected by high levels of statistically significant heterogeneity in this analysis. There was some evidence of increased patient satisfaction with home-based end of life care, and little evidence of the impact this form of care has on care givers. AUTHORS' CONCLUSIONS: The evidence included in this review supports the use of end of life home-care programmes for increasing the number of patients who will die at home, although the numbers of patients being admitted to hospital while receiving end of life care should be monitored. Future research should also systematically assess the impact of end of life home care on care givers.